Inflammation and Fibrogenesis in MAFLD: Role of the Hepatic Immune System - Torre, Pietro; Motta, Benedetta Maria; Sciorio, Roberta; Masarone, Mario; Persico, Marcello (Frontiers in Medicine, 2021)
Metabolic (dysfunction)-associated fatty liver disease (MAFLD) is the definition recently proposed to better circumscribe the spectrum of conditions long known as non-alcoholic fatty liver disease (NAFLD) that range from simple steatosis without inflammation to more advanced liver diseases. The progression of MAFLD, as well as other chronic liver diseases, toward cirrhosis, is driven by hepatic inflammation and fibrogenesis. The latter, result of a “chronic wound healing reaction,” is a dynamic process, and the understanding of its underlying pathophysiological events has increased in recent years. Fibrosis progresses in a microenvironment where it takes part an interplay between fibrogenic cells and many other elements, including some cells of the immune system with an underexplored or still unclear role in liver diseases. Some therapeutic approaches, also acting on the immune system, have been probed over time to evaluate their ability to improve inflammation and fibrosis in NAFLD, but to date no drug has been approved to treat this condition. In this review, we will focus on the contribution of the liver immune system in the progression of NAFLD, and on therapies under study that aim to counter the immune substrate of the disease.